Algorithm for Generating Text Descriptions of Bit Calendars - Hynek Bachraty; Emil Krsak; Marek Tavac (Communications - Scientific letters of the University of Zilina, 2009)
The article deals with the problematics of generating calendar text descriptions based on their bit map. We introduce the description of the algorithm we have designed, its basic ideas and parts. We also present the results of testing the successfulness of the algorithm before it is primarily used.